The Future Identity of Industrial Products and Their Variables (Al-Academy, 2025)
The research addressed the concept of "the future identity of industrial products and its variables," which reflects their continuous evolution under the influence of cultural, technological, and environmental factors. This concept is rooted in the philosophy of becoming, linking the past, present, and future, with a focus on the role of nostalgia (longing for the past) in reshaping identity by merging heritage elements with modern innovations. The research problem was formulated through the following question: What are the variables of the future identity of industrial products? A descriptive methodology was adopted to analyze the sample, and the researcher concluded that the design preserved BMW’s iconic luxurious and sporty identity while adapting it to global market demands for electric vehicles, such as adopting sleek aerodynamic lines that reflect modernity. It also provided advanced customization options, such as mood-adjustable LED lighting and integrated entertainment systems tailored to individual user preferences.. Results: - that the design preserved BMW’s iconic luxurious and sporty identity while adapting it to global market demands for electric vehicles, such as adopting sleek aerodynamic lines that reflect modernity. It also provided advanced customization options, such as mood-adjustable LED lighting and integrated entertainment systems tailored to individual user preferences